Effect of Invasive Mechanical Ventilation at Birth on Lung Function Later in Childhood - Di Filippo, Paola; Dodi, Giulia; Di Pillo, Sabrina; Chiarelli, Francesco; Attanasi, Marina (Frontiers in Pediatrics, 2022)
Background Despite recent neonatal care improvements, mechanical ventilation still remains a major cause of lung injury and inflammation. There is growing literature on short- and long-term respiratory outcomes in infants born prematurely in the post-surfactant era, but the exclusive role of mechanical ventilation at birth in lung function impairment is still unclear. The aim of this study was to assess the effect of neonatal mechanical ventilation on lung function parameters in children born ≤ 32 weeks of gestational age at 11 years of age. Materials and Methods In total, 55 ex-preterm children born between January 1, 2006 and December 31, 2007 were enrolled at 11 years of age. Neonatal information was obtained from medical records. Information about family and personal clinical history was collected by questionnaires. At 11 years of age, we measured spirometry parameters, lung volumes, diffusing lung capacity, and fractional exhaled nitric oxide. In addition, an allergy evaluation by skin prick test and eosinophil blood count were performed. A multivariable linear or logistic regression analysis was performed to examine the associations of mechanical ventilation with respiratory outcomes, adjusting for confounders (maternal smoking during pregnancy, gestational age, surfactant replacement therapy, and BMI). Results No difference in lung function evaluation between ventilated and unventilated children were found. No association was also found between mechanical ventilation with lung function parameters. Conclusion Mechanical ventilation for a short period at birth in preterm children was not associated with lung function impairment at 11 years of age in our study sample. It remains to define if ventilation may have a short-term effect on lung function, not evident at 11 years of age.